Life insurance: regulation as contract enforcement - Morrison, A (University of Oxford, 2004)
Debating the minutiae of insurance regulation without a clear understanding of why insurance companies are regulated is futile. In this non-technical essay I discuss the economic rationale for insurance business regulation. I conclude that the appropriate role of the regulator in this industry is to enforce contracts which would otherwise be broken. This implies that regulation should be optional, and that regulation need not be a monopoly activity.